The Development of Novel In Vitro Binding Assays to Further Elucidate the Role of tRNAs in Protein Synthesis - Bell, Anthony J.; Jr.; Ellzey, Suzanna; McDougald, Devin; Serrano, Crystal (IntechOpen, 2011)
None